Materializing poverty : how the poor transform their lives - Taylor, Erin B. (Anthropology of daily life series., 2013)
In this book, anthropologist Erin Taylor explores how residents of a squatter settlement in Santo Domingo, Dominican Republic, use their material resources creatively to solve everyday problems and, over a few decades, radically transform the community. Their struggles show how these everyday engagements with materiality, rather than more dramatic efforts, generate social change and build futures.